Strategies for Information Support of Vaccination - D. А. Adamov (Здоровье мегаполиса)
Purpose. The article analyzes modern strategies for vaccination information support regarding society digital transformation and misinformation spreading. The author examines the key areas of increasing vaccination population coverage: targeted campaigns, medical community partnership, public leaders and bloggers involvement, methods of storytelling and visual communication usage. Results. The article emphasizes the necessity of a personalized approach to different groups and the importance of sustainable trust, dialogue and interdisciplinary collaboration. The conclusion is based on analyzing foreign and Russian experience, regulatory framework and empirical data, it demonstrates the need for a systematic communication policy in public health.